SDN security control and forwarding method based on cipher identification - Xi QIN; Guodong TANG; Chaowen CHANG (Tongxin xuebao)
Aimed at the limited matching fields and the lack of effective data source authentication mechanism in the software defined networking (SDN),a SDN security control forwarding method based on cipher identification was proposed.First,the cipher identification was generated according to the user identity,file attributes or business content and other characteristics,and the data stream was marked by the cipher identification and signed with the private key based on the cipher identification.Then,when the data stream entered and left the network,the forwarding device verified its signature to ensure the authenticity of the data.At the same time,the cipher identification was designed as a matching item recognized by the forwarding device,and the network forwarding behavior was defined based on the cipher identification,so a fine-grained network control capability could be formed based on people,things,and business flow.Finally,the validity of the method is verified by experimental analysis.